POTENSI ANCAMAN BANJIR BANDANG SUB DAS TIMANG GAJAH KABUPATEN BENER MERIAH DAN ACEH TENGAH - Rahmi Nia Ivana; Eldina Fatimah; Azmeri Azmeri (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2021)
Timang Gajah Sub Watershed is one of total 12 sub watersheds located in Peusangan Watershed. The condition of Peusangan Watershed is degraded and it triggers hydrometeorology disaster such as flash flood. The record of flash flood events is very high in the districts located in Peusangan watershed. According to BPS 2014 Data, there were 32 events of flash flood occurred in Central Aceh, 17 events occurring in Bener Meriah, 7 events occurring in Bireuen, 2 events occurring in North Aceh, 23 events occurring in Pidie and 4 event occurring in Nagan Raya. This reason becomes the background of the research as well as there has not been compiled flash flood hazard map in Timang Gajah Sub Watershed. This research aims to compile flash flood hazard map in Timang Gajah Sub Watershed. The research analysis is by using Indonesia Disaster Risk (RBI) (2016). The analysis tool used is GIS tool. The result uses fuzzy membership analysis of inundation depth. Based on the analysis outcomes, it is resulted that flash flood hazard analysis in Timang Gajah Sub Watershed consist of 4 categories dominated by safe area as 29,366.55 Ha (81.89%) and vulnerable area as 2,954.83 Ha (8.24 %).